2020
DOI: 10.2147/rmhp.s266342
|View full text |Cite
|
Sign up to set email alerts
|

<p>Food Hygiene Practices and Associated Factors Among Food Handlers Working in Food Establishments in the Bole Sub City, Addis Ababa, Ethiopia</p>

Abstract: Background: Consumers' health would be at risk unless food preparation and handling hygiene is ensured by food establishments. Literature indicates that poor food handling and sanitation practices are more common among food handlers in developing countries resulting in food-borne illness. Hence, food handlers can play a significant role in ensuring food hygiene. To this end, the paper aims to assess the level of food hygiene practices and its associated factors of food handlers working in food establishments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
6

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 11 publications
10
38
6
Order By: Relevance
“…In this study, a good attitude towards food safety was also a significant predictor of good food safety practices. This finding is in line with results from cross-sectional studies conducted in Bole Sub-city, Addis Ababa, 18 Northwest Ethiopia, 20 Debarq Town 29 and Debre Markos Town, Ethiopia, 31 Imo State, Nigeria, 27 Kuwait, 40 Lahore, Pakistan, 28 and Sarawak and Petaling Jaya, Malaysia. 38 , 39 A possible reason for this association is that training in food safety measure packages leads to a good attitude, which may improve the behavior around and practice of food safety.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, a good attitude towards food safety was also a significant predictor of good food safety practices. This finding is in line with results from cross-sectional studies conducted in Bole Sub-city, Addis Ababa, 18 Northwest Ethiopia, 20 Debarq Town 29 and Debre Markos Town, Ethiopia, 31 Imo State, Nigeria, 27 Kuwait, 40 Lahore, Pakistan, 28 and Sarawak and Petaling Jaya, Malaysia. 38 , 39 A possible reason for this association is that training in food safety measure packages leads to a good attitude, which may improve the behavior around and practice of food safety.…”
Section: Discussionsupporting
confidence: 90%
“…The odds of performing good food safety practices among the study participants who had good knowledge of food safety practices was 2.05 times higher than in respondents who had poor knowledge. This study finding was also seen in previous studies carried out in Shashemene Town, Central Ethiopia, 26 Bole Sub-city, Addis Ababa, 18 Debre Markos Town, Ethiopia, 31 Dangila Town, 30 Gondar City, 7 and Debarq Town, Northwest Ethiopia, 29 Ghana, 1 Imo State, Nigeria, 27 Bangladesh, 34 Jordan, 37 and Sarawak and Petaling Jaya, Malaysia. 38 , 39 This association indicated that food safety practices are highly influenced by increasing knowledge scores regarding food safety.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The socio-economic situation and rapid urbanization in developing countries, particularly Togo, have facilitated the emergence of new consumption patterns. With the exception of the home, collective catering services are the busiest places of consumption (Abdi et al, 2020). The formal sector, characterized by a much more modern catering industry in hotels, restaurants and canteens where people of a high standard of living, living and working in the cities, often feed themselves.…”
Section: Introductionmentioning
confidence: 99%